PPEF2 Opposes PINK1-Mediated Mitochondrial Quality Control by Dephosphorylating Ubiquitin - Christopher E. Wall; Christopher M. Rose; Max Adrian; Yi J. Zeng; Donald S. Kirkpatrick; Baris Bingol (Cell Reports, 2019)
Summary: Dysregulation of mitophagy, whereby damaged mitochondria are labeled for degradation by the mitochondrial kinase PINK1 and E3 ubiquitin ligase Parkin with phosphorylated ubiquitin chains (p-S65 ubiquitin), may contribute to neurodegeneration in Parkinson’s disease. Here, we identify a phosphatase antagonistic to PINK1, protein phosphatase with EF-hand domain 2 (PPEF2), that can dephosphorylate ubiquitin and suppress PINK1-dependent mitophagy. Knockdown of PPEF2 amplifies the accumulation of p-S65 ubiquitin in cells and enhances baseline mitophagy in dissociated cortical cultures. Overexpressing enzymatically active PPEF2 reduces the p-S65 ubiquitin signal in cells, and partially purified PPEF2 can dephosphorylate recombinant p-S65 ubiquitin chains in vitro. Using a mass spectrometry approach, we have identified several p-S65-ubiquitinated proteins following mitochondrial damage that are inversely regulated by PPEF2 and PINK1. Interestingly, many of these proteins are involved in nuclear processes such as DNA repair. Collectively, PPEF2 functions to suppress mitochondrial quality control on a cellular level through dephosphorylation of p-S65 ubiquitin. : Wall et al. identify PPEF2 as a phosphatase that can dephosphorylate p-S65 ubiquitin and suppress mitophagy. PPEF2 regulates mitophagy at baseline, which has pronounced activity in astrocytes. They also identify proteins that are p-S65-ubiquitinated in response to mitochondrial damage, several of which are involved in DNA repair inside the nucleus. Keywords: Parkinson’s disease, mitochondria, mitophagy, PINK1, Parkin, PPEF2, ubiquitin